STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH INKLUSI - Rofaidah Ansyoriyah; Maftuh Maftuh (JURNAL ILMIAH NUSANTARA, 2024)
The importance of studying religion has a very broad meaning, regardless of whether a person's condition is normal or has mental, physical or behavioral limitations. Children who have these limitations also have the right to get the same education as normal children in general. Therefore, one of the government's efforts to make this happen is by holding inclusive education. Like SDN Klampis Ngasem I/246 Surabaya which is a school with inclusive education services. This school is growing rapidly with adequate infrastructure and activities and learning in accordance with the characteristics of true inclusive education. The results showed that the learning strategy for Islamic religious education at SDN Klampis Ngasem I/246 Surabaya was to use the Dick and Carey approach. This is evident from the results of the interviews and observations that the researchers conducted, which stated that there were five stages in the learning strategy. The five stages include: First, preliminary learning. Second, delivery of information, Third, student participation, Fourth, evaluation. Fifth, preliminary learning. To achieve the learning objectives of Islamic religious education as effectively as possible, it is necessary to optimize supporting factors and minimize the occurrence of inhibiting factors that prevent learning from running optimally.